The Relationship Between Early MP-ASI and Stunting Incidence in Children Aged 2-3 Years - Evada Safitri; Wiwin Reni Rahmawati; Tulus Puji Hastuti; Ribkha Itha Idhayanti (Midwifery and Nursing Research, 2023)
Background: Complementary food for breast milk (MP-ASI) is additional food given after the baby is more than six months old as a complementary food to breast milk until the age of two years. MP-ASI given before the baby is six months old can cause infection in the baby's digestive tract so that the baby experiences interference with the absorption of nutrients for growth and development so that the baby experiences stunting. Stunting is a condition of chronic malnutrition that is characterized by height or body length that is not in accordance with age or shorter than the normal number. The stunting rate in Banyumas in 2019 reached 16,581 cases. The purpose of this study was to determine the relationship between early complementary feeding and the incidence of stunting in children aged 2-3 years in Gunung Wetan village Jatilawang district Banyumas district. Methods: cross sectional method. The population in this study was 76 mothers who had children aged 2-3 years. The sample of this study was 36 people. The sampling technique of this study used a purposive sampling technique. The statistical test in this study uses the coefficient-contingency. Results: The results of this study indicate that there is a relationship between early complementary feeding and the incidence of stunting in children aged 2-3 years, with a p value of 0.003. Based on this study, it can be concluded that early complementary feeding has a relationship with the incidence of stunting in children aged 2-3 years in Gunung Wetan Village Jatilawang district Banyumas district. Conclusion: It is hoped that parents can understand the impact of early complementary feeding as a cause of stunting in children. So that children can be fulfilled with nutrition for their growth and development